2013
DOI: 10.1093/acprof:oso/9780199674701.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Econophysics and Physical Economics

Abstract: An understanding of the behaviour of financial assets and the evolution of economies has never been as important as it is today. This book looks at these complex systems from the perspective of the physicist. So-called ‘econophysics’ and its application to finance have made great strides in recent years. Less emphasis has been placed on the broader subject of macroeconomics, and many economics students are still taught traditional neo-classical economics. The reader is given a general primer in statistical phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 98 publications
3
39
0
Order By: Relevance
“…However, it has been after the works by Stanley et al [29] when the number of research papers published by physicists, in economics in general and in finance in particular, has become relevant. Other achievements such as the generalized autoregressive conditional heteroskedasticity (GARCH) model or the Black-Scholes equation helped in the rise of the field known as econophysics, which aims to employ physical theories and models in finance [30][31][32][33][34]. Still, when considering a physical scope, market dynamics is not fully understood; usually, stochastic processes, statistical mechanics, or nonlinear physics are considered when describing market dynamics, but a unified body that describes the equivalence between mass or lengths with financial magnitudes is lacking.…”
mentioning
confidence: 99%
“…However, it has been after the works by Stanley et al [29] when the number of research papers published by physicists, in economics in general and in finance in particular, has become relevant. Other achievements such as the generalized autoregressive conditional heteroskedasticity (GARCH) model or the Black-Scholes equation helped in the rise of the field known as econophysics, which aims to employ physical theories and models in finance [30][31][32][33][34]. Still, when considering a physical scope, market dynamics is not fully understood; usually, stochastic processes, statistical mechanics, or nonlinear physics are considered when describing market dynamics, but a unified body that describes the equivalence between mass or lengths with financial magnitudes is lacking.…”
mentioning
confidence: 99%
“…Several analyses of personal income distributions have found that the low-to-middle-income part of the distribution decays exponentially and that the high-income tail decays like a powerlaw [30,74]. Based on these analyses, various econophysics models have been propopsed with the goal of generating distributions of income with two-part shapes in which the lower-to-middle part of the income distribution follows an exponential distribution, and the upper tail follows a power-law distribution [39,80,81]. Among the models that generate a distribution of income or wealth as a self-organizing process based on interactions between individuals, several are able to produce either a power-law decay in the upper tail, or an exponential decay in the lower part of the distribution, but not both.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot interfere with σ S,dis , which consists of the vectorial generalized currents and forces shown in Equation (5). Therefore, Equation (4) requires that σ S,chem > 0 and σ S,dis > 0, separately .…”
Section: Dissipationmentioning
confidence: 99%